Exploring Interrater Disagreement on Essential Tremor Using a Standardized Tremor Elements Assessment. Issue 3 (12th February 2021) - Becktepe, Jos; Gövert, Felix; Balint, Bettina; Schlenstedt, Christian; Bhatia, Kailash; Elble, Rodger; Deuschl, Günther
Abstract: Background: Patients with upper limb action tremor frequently exhibit additional neurological signs of uncertain significance. Clinicians vary in their interpretation, and interrater agreement on the final diagnosis is poor. Objectives: A new clinical tool for assessing the presence or absence of clinical signs that are important in axis‐1 classification of tremor patients is introduced: the Standardized Tremor Elements Assessment (STEA). Interrater agreement is determined, and signs leading to disagreement in the final diagnosis are identified. Methods: Three tremor‐focussed and one dystonia‐focussed movement disorder specialists rated 59 videos of patients with upper limb action tremor syndromes using STEA. Interrater agreements for final diagnosis and STEA items were calculated. Results: Interrater agreement regarding the final diagnosis was higher within the group of tremor specialists and poor between dystonia and tremor specialists. Greater agreement was found for items characterizing tremor than for signs of dystonia. Conclusions: Clinical signs leading to diagnostic disagreement were identified with STEA, and STEA should therefore be useful in future studies of diagnostic disagreement. The thresholds for considering neurological signs as soft versus significant for ataxia, parkinsonism, dystonia, etc. are critically important in tremor classification and must be studied across movement disorder subspecialties, not simply within a pool of tremor specialists.